Immunocytochemical study of estrogen receptor activation factor (E-RAF) and the proteins that interact with nuclear estrogen receptor II (nER II) in epithelial endometrial cells, in the presence and in the absence of estradiol - OM Echeverría; RV Thampan; S Juárez-Chavero; AD Hernández-Pérez (European Journal of Histochemistry, 2009)
The localization and abundance of the estrogen receptor activation factor (E-RAF) and a small nuclear ribonucleoprotein (snRNP) complex containing three proteins, p32, p55 and p60, which interact with the nuclear estrogen receptor II (nER II), have been studied in rat endometrial epithelial cells by means of immunofluorescence and high resolution quantitative immunocytochemistry. In the cytoplasm E-RAF is associated with the rough endoplasmic reticulum. In the nucleus it is mainly localized at the interchromatin space, and surrounding the clumps of compact or semi-condensed chromatin. Quantitative analyses show that the abundance of E-RAF in the nucleus increases after ovariectomy and decreases 3 minutes after estradiol administration. These results are in agreement with the currently available biochemical data. Double immunolocalizations demonstrate that p32, p55, p60 co-localize with other splicing-related protein. High resolution immunolocalization shows that p32, p55, p60 are associated with perichromatin fibrils (co-transcriptional splicing) and with clusters of interchromatin granules (storage of splicing-related molecules). The nuclear abundance of the snRNP complex decreases with ovariectomy, increases within 3 minutes after estradiol administration and remains higher than that in ovariectomized animals for 27 minutes. These results strongly support the previous data on the role of nER-II in the regulation of mRNA transcription and its export from the nucleus to the cytoplasm.